2019
DOI: 10.1186/s13287-019-1347-1
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of MHC-mismatched mouse embryonic stem cell-derived thymic epithelial progenitors and MHC-matched bone marrow prevents autoimmune diabetes

Abstract: Background Type 1 diabetes (T1D) is an autoimmune disease resulting from the destruction of insulin-secreting islet β cells by autoreactive T cells. Non-obese diabetic (NOD) mice are the widely used animal model for human T1D. Autoimmunity in NOD mice is associated with particular major histocompatibility complex (MHC) loci and impaired islet autoantigen expression and/or presentation in the thymus, which results in defects in both central and peripheral tolerance. It has been reported that induct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…We aimed to build an in vitro model of cell-to-cell communication through EVs and soluble proteins. To demonstrate the functional transfer between embryonic trophectoderm and maternal MSC of protein-containing secretome, we first confirmed that EVs isolated from conditioned media of BBT cells previously labeled with PKH26 were successfully uptaken by maternal eMSC and pbMSC during a chemotaxis experiment in an agarose spot assay following the procedures of Calle et al [ 11 , 15 ] and Monguió-Tortajada et al [ 16 ] as described in materials and methods ( Figure S5 ).…”
Section: Resultsmentioning
confidence: 81%
See 4 more Smart Citations
“…We aimed to build an in vitro model of cell-to-cell communication through EVs and soluble proteins. To demonstrate the functional transfer between embryonic trophectoderm and maternal MSC of protein-containing secretome, we first confirmed that EVs isolated from conditioned media of BBT cells previously labeled with PKH26 were successfully uptaken by maternal eMSC and pbMSC during a chemotaxis experiment in an agarose spot assay following the procedures of Calle et al [ 11 , 15 ] and Monguió-Tortajada et al [ 16 ] as described in materials and methods ( Figure S5 ).…”
Section: Resultsmentioning
confidence: 81%
“…Recently, our group characterized for the first time endometrial mesenchymal stem cell lines (eMSC) [ 11 ] as well as peripheral blood MSC (pbMSCs) lines [ 12 ]. While eMSC showed a reduced migratory capacity in response to the implantation cytokine IFN-τ [ 11 ], pbMSC showed chemotactic behavior to both inflammation (TNFα, IL1β), embryo implantation stimuli (IFN-τ) or BBT-secretome, suggesting that the embryo secretome plays a role in ensuring the retention of eMSC and the active recruitment of MSCs from bone marrow during early pregnancy to repress the immune response to prevent the embryo rejection by the maternal organism [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations